HUBUNGAN USIA MENARCHE, STATUS GIZI, ASUPAN KALSIUM DAN ZAT BESI DENGAN KEJADIAN DYSMENORRHEA (NYERI HAID) PADA REMAJA PUTRI DI SMPN 1 PABUARAN KAB. SERANG - Mulyani, Ira Suci; Amaliah, Lili; Perdana, Fachruddin (Jurnal Andaliman: Jurnal Gizi Pangan, Klinik dan Masyarakat, 2023)
Adolescence, especially Junior High School (SMP) age, is the early age of adolescents experiencing puberty for women which is marked by menstruation, often pain is felt when that period occurs, many factors influence this pain, one of which is nutrient intake and calcium. This study aims to determine the relationship between menarche age, nutritional status, calcium, and iron intake with the incidence of dysmenorrhea (menstrual pain) at SMPN 1 Pabuaran. The research design used is a correlation descriptive study with a cross sectional approach. The research results obtained using the Spearman Rank test showed that the relationship between age and the incidence of dysmenorrhea had a p-value of 0.789> 0.05, so the result was that there was no relationship between age and the incidence of dysmenorrhea, then the relationship between nutritional status and the incidence of dysmenorrhea obtained a p-value of 0.806> 0.05 means there is no relationship, then the relationship between calcium and the incidence of dysmenorrhea obtained a p-value of 0.000 <0.05, where the result is a relationship between iron intake with dysmenorrhea. From the results of the study it was found that there was no relationship between age and nutritional status and from the calcium and iron variables there was a relationship with a p-value <0.05.Keywords: Age of menarche, nutritional status, iron, calcium, dysmenorrhea, young women, menstrual pain